Viewpoint Objects Never? Well, Hardly Ever! - Ben-Ari, Mordechai (Communications of the ACM, 2010)
The article presents a critique of object-oriented programming (OOP), noting that it has been widely promoted as a dominant method in the field of computer software development, but has not proved as useful as its proponents allege. The author notes that his experience using and teaching OOP has not convinced him of the method's utility. An example involving the development of embedded software for automobiles is presented, to illustrate the irrelevance of OOP in this context.